A case with bilateral C-shaped autofluorescence in retinal degeneration - Hsin Hsu; Chunya Kang; Eugene Yu-Chuan Kang; Nan-Kai Wang (American Journal of Ophthalmology Case Reports)
Purpose: To report a case of a 19-year-old male with Optic Atrophy-13 (OPA13) associated with a de novo heterozygous missense variant in the single-strand DNA-binding protein 1 (SSBP1) gene, characterized by a bilateral double C-shaped hyper-autofluorescent ring on fundus autofluorescence (FAF). Observations: A 19-year-old male exhibited poor visual acuity, pale optic discs, vessel attenuation, and peripheral pigmentary changes. FAF imaging revealed a bilateral double C-shaped hyper-autofluorescent ring, which was not frequently observed. Optical coherence tomography (OCT) showed retinal thinning and ellipsoid zone disruption, while electroretinography (ERG) indicated cone-rod dystrophy. Genetic testing identified a pathogenic SSBP1 missense variant, confirming the diagnosis of OPA13. Parental genetic analysis excluded the variant, establishing it as a de novo one. Conclusions and importance: This report highlights a novel retinal feature—a double C-shaped autofluorescent ring—associated with OPA13, potentially serving as a diagnostic marker for the disease. The findings emphasize the role of genetic testing in diagnosing OPA13 and distinguishing it from other retinal and optic neuropathies. Recognition of this feature could enhance early diagnosis and management strategies for patients with suspected OPA13.